2017
DOI: 10.1111/tan.12946
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a 10/10 matched donor for patients with an uncommon haplotype is unlikely

Abstract: Therefore, the HLA HFD that informs the HapLogic matching algorithm is thorough as UPH patient searches were infrequent. Since such patients are highly unlikely to have a fully 10/10 matched URD identified, this study supports the identification of alternative stem cell sources including cord blood or a mismatched URD early in the search process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
2
6
0
1
Order By: Relevance
“…In the unrelated setting, the probability of finding a 10/10 matched donor is largely determined by haplotype frequencies, our analyses thus agree with previous publications [13,[27][28][29][37][38][39]. Accurate prediction allows to define the optimal strategy to find the best suitable donor, whether a matched unrelated, mismatched unrelated or a haploidentical donor [40,41].…”
Section: Discussionsupporting
confidence: 87%
“…In the unrelated setting, the probability of finding a 10/10 matched donor is largely determined by haplotype frequencies, our analyses thus agree with previous publications [13,[27][28][29][37][38][39]. Accurate prediction allows to define the optimal strategy to find the best suitable donor, whether a matched unrelated, mismatched unrelated or a haploidentical donor [40,41].…”
Section: Discussionsupporting
confidence: 87%
“…identifying matched donors 1,7,[12][13][14][15][16] which led to the development of various software programs computing the likelihoods to identify donors with suitable matching criteria. [17][18][19][20] With the increasing diversity of HLA haplotypes across Europe, 3,4,21 the need for continuing growth of small/intermediate size registries has become more obvious. 22 However, with few exceptions 9,23,24 no detailed analysis has been performed on the selected donors with respect to HLA and non-HLA characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the direct link between haplotype frequencies in different HSC registries and the probabilities of identifying matched donors which led to the development of various software programs computing the likelihoods to identify donors with suitable matching criteria . With the increasing diversity of HLA haplotypes across Europe, the need for continuing growth of small/intermediate size registries has become more obvious .…”
Section: Discussionmentioning
confidence: 99%
“…This delay can adversely affect transplant outcomes and has special relevance for patients of non-European or mixed ancestries. Such patients due to diverse HLA haplotypes, lesser registry representation, and lower rates of donor availability are far less likely to identify donors who are HLA-matched 11-13 . It can also adversely affect the care of patients in need of urgent transplantation as disease status at the time of transplant is an important determinant of survival in patients with hematologic malignancies (reviewed in Lown et al 14 and references 15-17 ).…”
Section: Introductionmentioning
confidence: 99%